Facebook usage pattern among rural youths of 1Malaysia Wireless Village - Sahharon, Hamizah; Bolong, Jusang; Omar, Siti Zobidah; Mohamed Shaffril, Hayrol Azril (Human Resource Management Academic Research Society, 2018)
The aim of this study is to discover the pattern of Facebook usage among the rural youths of 1Malaysia Wireless Village in Malaysia. Technology Acceptance Model and the Theory of Social Categorization were used to further explain their Facebook usage and the benefits of Facebook functionality in attaining a virtual community among rural youths to make them feel social bonding. This study is quantitative in nature and a survey method was adopted by using a questionnaire to collect the data. Results show that rural youths would continuously use multiple platforms to get connected to Facebook. The rural youths of 1Malaysia Wireless Village have a high Facebook usage acceptance and have frequently used the five main Facebook functionalities; such as group, conversation, sharing, identity and reputation to sustain their interpersonal relationships between close and distant friends. Several recommendations were made to ensure positive utilization of Facebook in enhancing the social context of rural youths’ social interaction.